THE CORRELATION BETWEEN STUDENTS' READING HABITS AND VOCABULARY MASTERY TOWARD THEIR WRITING ABILITY AT TENTH CLASS OF SMAN 2 NGANJUK - Dinan Izzazi Zatalini; Sujono (STKIP PGRI Nganjuk, 2023)
The objectives of the research are: 1) To measure the level of students’ reading habits, vocabulary mastery, and writing ability of tenth class of SMAN 2 Nganjuk in the academic year 2022/2023, 2) To find out the correlation between students' reading habits and vocabulary mastery toward their writing ability of tenth class of SMAN 2 Nganjuk in the academic year 2022/2023. The research using quantitative methods and designed as correlational research. The population of this research consisted of all tenth grade students of SMAN 2 Nganjuk for the academic year 2022/2023. The sample used were 34 students of X-7 class. In collecting data, this research using questionnaire and test. The data analysis technique used are descriptive statistics, inferential statisics using multiple correlation and statistical F-test analysis. The result of this study showed that the reading habit at tenth class of SMAN 2 Nganjuk is in good category with average score is 61,73. The students’ vocabulary mastery is in low category with the average score is 58,24. The writing ability of students is standard/average with average score is 63,53. Based on the result of the analysis with significance level 5%, the value of Fcount (8,75) > Ftable (3,30). The alternative hypothesis (H1) is accepted, which means there is a significant correlation between students’ reading habit and vocabulary mastery toward their writing ability of tenth class students of SMAN 2 Nganjuk. Tujuan penelitian ini adalah: 1) Untuk mengukur tingkat kebiasaan membaca siswa, penguasaan kosakata siswa, dan kemampuan menulis siswa, 2) Untuk mengetahui korelasi antara kebiasaan membaca siswa dan penguasaan kosakata terhadap kemampuan menulis mereka pada kelas sepuluh SMAN 2 Nganjuk Tahun Pelajaran 2022/2023. Penelitian menggunakan metode kuantitatif dan didesain sebagai penelitian korelasional. Populasi pada penelitian ini terdiri dari seluruh siswa kelas sepuluh SMAN 2 Nganjuk Tahun Pelajaran 2022/2023. Sampel yang digunakan adalah 34 siswa dari kelas X-7. Dalam mengumpulkan data, penelitian ini menggunakan kuesioner dan tes. Teknik analisis data yang digunakan adalah statistik deskriptif, statistik inferensial menggunakan korelasi ganda dan analisis statistik F-tes. Hasil penelitian menunjukkan bahwa kebiasaan membaca di kelas sepuluh SMAN 2 Nganjuk dalam kategori baik dengan nilai rata-rata 61,73. Penguasaan kosakata siswa dalam kategori rendah dengan nilai rata-rata 58,24. Kemampuan menulis siswa standar/rata-rata dengan nilai rata-rata 63,53. Berdasarkan hasil analisis dengan taraf signifikan 5%, nilai Fhitung (8,75) > Ftabel (3,30). Hipotesis alternatif (H1) diterima yang berarti ada korelasi yang signifikan antara kebiasaan membaca siswa, penguasaan kosakata, dan kemampuan menulis pada kelas sepuluh SMAN 2 Nganjuk Tahun Pelajaran 2022/2023.